2021
DOI: 10.1088/2516-1075/abfd21
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding in biocompatible ionic liquids: an ab-initio characterization of dimeric interactions

Abstract: CO 2 capture at the production site represents one of the accessible ways to reduce its emission in the atmosphere. In this context, CO 2 chemisorption is particularly advantageous and is often based on exploiting a liquid containing amino groups that can trap CO 2 due their propensity to react with it to yield carbamic derivatives. A well-known class of ionic liquids based on amino acids anions might represent an ideal medium for CO 2 capture because, at difference with present implementations, they are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…Donne et al. performed ab2.5ptinitio ${ab\hskip0.25eminitio}$ MD simulations to evaluate inter‐atomic forces between different deprotonated amino acids and cholinium cations [74] . Their analysis revealed that the amino acid anions incorporated both hydrogen bond donors and acceptors result in strong hydrogen bonding interactions between the anions.…”
Section: Discussionmentioning
confidence: 99%
“…Donne et al. performed ab2.5ptinitio ${ab\hskip0.25eminitio}$ MD simulations to evaluate inter‐atomic forces between different deprotonated amino acids and cholinium cations [74] . Their analysis revealed that the amino acid anions incorporated both hydrogen bond donors and acceptors result in strong hydrogen bonding interactions between the anions.…”
Section: Discussionmentioning
confidence: 99%
“…4. 160,162,165,[168][169][170][171] Other interactions have also been explored by Bodo's group, who calculated dimers of different amino acid anions and zwitterions. 170,172 They noticed aggregation phenomena among anions, enabled by H-bonds between the amine and carboxylate groups.…”
Section: Design Rules For Chaail-based Solutionsmentioning
confidence: 99%